2017
DOI: 10.1007/s00464-017-5730-7
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term outcomes of laparoscopic gastrectomy versus open gastrectomy in patients with clinically and pathological locally advanced gastric cancer: a propensity-score matching analysis

Abstract: LG can be a feasible treatment that is beneficial in terms of earlier recovery after operation and can be expected to result in similar survival as OG in patients with AGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
12
34
0
3
Order By: Relevance
“…The objective of the present study was to analyse the practicability, safety and oncological quality of laparoscopic surgery for gastric cancer in a typical cohort of patients under conditions prevalent in the West, as well as to verify the reproducibility of data from Asia [10,12,18,19]. By comparison with Asian patients with similarly treated UICC stages, our patients were not only 5-10 years older on average, but also exhibited greater co-morbidity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The objective of the present study was to analyse the practicability, safety and oncological quality of laparoscopic surgery for gastric cancer in a typical cohort of patients under conditions prevalent in the West, as well as to verify the reproducibility of data from Asia [10,12,18,19]. By comparison with Asian patients with similarly treated UICC stages, our patients were not only 5-10 years older on average, but also exhibited greater co-morbidity.…”
Section: Discussionmentioning
confidence: 89%
“…Anastomosis failure developed in 2 % of the LG group and in 6 % of the OG group. 30-day mortality was zero [18]. In a Chinese prospective randomised study with 519 LG and 520 OG, Hu et al recorded an overall morbidity of 14.9 % in the LG group and 12.9 % in the OG group (p = 0.314).…”
Section: Discussionmentioning
confidence: 96%
“…What is more, conclusions from retrospective or prospective studies even meta-analyses [26, 27] concerning this topic were inconsistent. Some literature concluded that LADG was associated with a lower postoperative complication rate in AGC patients [26, 27]; others found no significant difference between LADG and ODG concerning postoperative morbidity [14, 28]. Even a meta-analysis reported by Cochrane Database considered that the evidence qualities of most completed or ongoing RCTs were low because of high risks of bias [29].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available data indicate that in addition to the advantages of minimally invasive surgery, such as rapid recovery, reduced blood loss, less pain, and fewer surgical site complications, laparoscopic gastric cancer surgery also provides acceptable oncological outcomes. [11][12][13][14][15][16] In our clinic, we try to utilize laparoscopic approaches in gastroenterologic cancer surgery as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diffi- culty of applying purse-string sutures to the esophagus during anvil placement in laparoscopic surgery is one of the reasons alternative methods have been sought. [15,21] The linear stapler technique may be difficult for inexperienced surgeons because it requires greater mobilization of the esophagus and suturing of the stapler entry site. However, advantages of this technique are that the linear stapler is more suitability for insertion through a trocar, and an experienced surgeon can perform the anastomosis more easily using a linear stapler than a circular stapler.…”
Section: Discussionmentioning
confidence: 99%